Efficient simulation of flame acceleration and deflagration-to-detonation transition in smooth pipes. (July 2021) - Wieland, C.; Scharf, F.; Schildberg, H.-P.; Hoferichter, V.; Eble, J.; Hirsch, C.; Sattelmayer, T.
Abstract: Evaluation of accident scenarios including flame acceleration and deflagration-to-detonation transition (DDT) in chemical plant piping systems increases the need for an efficient numerical simulation tool capable of dealing with this phenomenon. In this work, a hybrid pressure-density-based solver including deflagrative flame propagation as well as detonation propagation is presented. The initial incompressible acceleration stage is covered by the pressure-based solver until the flame velocity reaches the fast flame regime and transition to the density-based solver is done. The deflagration source term is formulated in terms of a turbulent flame speed closure model incorporating various physical effects crucial for flame acceleration at low turbulence conditions (Katzy and Sattelmayer, 2018). Modelling of the detonation source term is based on a quadratic heat release function (Hasslberger, 2017). The presented numerical approach is validated in terms of DDT locations and pressure data from Schildberg (2015) as well as recently completed flame tip position measurements. For this purpose, H2 /O2 /N2 mixtures ranging from 25.6 vol-% H2 to 29.56 vol-% H2 in two different pipe geometries are considered. The focus of the current work is on predicting the DDT location correctly and good agreement is observed for the investigated cases. Highlights: Efficient CFD solver for simulating flame acceleration and DDT of hydrogen mixtures in smooth pipes. Hybrid pressure-density-based solver architecture allows to efficiently simulate the whole process of flame acceleration. Most important features of flame propagation as formation of a tulip flame can be reproduced.